Effect of Using PID Control in Switched Inductor Boost Converter - Mochamad Shofwan Rizqulloh; Unggul Wibawa; Lunde Ardhenta; Alisa Zahrani Farady Daud (Department of Electrical Engineering Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Among the different kinds of boost converters is the switched inductor boost converter. But the Switched Inductor Boost Converter still has drawbacks, like output voltage results that still overshoot, a lengthy time to attain a steady state, and output voltage that fluctuates in response to input voltage changes. This shortcoming can be addressed in this investigation by using a PID controller. The PID parameter is obtained using the Direct Synthesis method, which includes Kp, Ki, and Kd. The state space averaging method is employed for the converter modeling. By applying the PID controller to the Switched Inductor Boost Converter while simulation is carried out using MATLAB-Simulink, the output voltage's transient response is improved where PID control can eliminate overshoot on output voltage response and speed up settling time by 1.35 times and also improves system's resistance to variations in input voltage and load value, allowing it to sustain the output voltage and lower momentary voltage change up to 68.3045% and speeds up recovery time up to 2.5287 times faster when input voltage changes occurs and lower overshoot value up to 39.2809% and speeds up recovery time up to 2.708 times faster when load changes occurs.